Challenges for early diagnosis of neonatal herpes infection in Japan - Kojima, Junya; Suzuki, Shunji; Hoshi, Shin-Ichi; Sekizawa, Akihiko; Sagara, Yoko; Matsuda, Hideo; Ishiwata, Isamu; Kitamura, Tadaichi (Frontiers in Reproductive Health, 2024)
BackgroundThis study aimed to analyze the recent prevalence of neonatal herpes simplex virus infection, maternal symptoms in the presence of neonate who has herpes simplex virus infection, and mode of delivery in Japan.MethodsWe requested 2.078 obstetrical facilities that are members of the Japan Association of Obstetricians and Gynecologists (JAOG) to provide information on neonatal herpes simplex virus infection involving deliveries at or after 22 weeks of gestation between 2020 and 2022. Of these, 1.371 (66.0%) facilities responded with information that could undergo statistical analysis.ResultsThere were 10 cases of neonatal herpes simplex virus infection, and the incidence of neonatal herpes simplex virus infection in Japan was about 1 in 1.4 × 105 live births. There were no characteristic maternal findings common to cases of neonatal herpes simplex virus infection.ConclusionThe incidence of neonatal herpes simplex virus infection in Japan was low. We could not identify any characteristic maternal findings common to cases of neonatal herpes simplex virus infection.